Assessment of factors for the increase in the productivity of grain crops - Petrova Svetlana (EDP Sciences, 2021)
Grain production is a strategic element of the agricultural and food complex in Russia, which predetermines its fundamental importance in food security. The task of the increase in the level of grain yields is still urgent, despite the full satisfaction of the needs of the domestic market of Russia due to the benefits from grain exports. The authors assess the influence of the intensification processes on yield level taking into account the elimination of the influence of scale factor. During the research such statistical methods as correlation-regression and cluster were used as analysis tools. The authors revealed a pattern that a higher level of production costs per 1 hectare of grain crops provided a correspondingly higher yield. In the context of total large grain-sowing companies with an area of crops from 4 to 11 thousand hectares, a relatively high elasticity of production costs was revealed (0.87), which was higher than in the group of medium-sized companies (from 2 to 4 thousand hectares) by 0, 37 points. The scale factor had a significant influence on the intensification process and on the yield respectively. The model of the relationship between the size of cultivated areas and the yield of grain crops was qualitatively described by a parabola with a high degree of stochastic relationship. The maximum yield value was reached by a group of large grain-sowing companies with an area of crops from 5 to 10 thousand hectares, while in very large agricultural companies the yield was lower and was at the average level for the region.